A QUESTIONNAIRE-BASED STUDY TO ASSESS THE AWARENESS OF MATERIOVIGILANCE AMONG HEALTH-CARE PROFESSIONALS WORKING IN A TERTIARY CARE TEACHING HOSPITAL IN THE KURNOOL DISTRICT - MANDANNA, SANGALA SRIMANTH; KR, SURESHA; REDDY S, NARAYANA; RAJU, SAMBA SIVA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Materiovigilance (MV) is the coordinated system of identification, collection, reporting, and analysis of untoward occurrences associated with the use of medical devices (MD) and enhancing patients safety, also preventing their recurrence by health-care professionals (HCPs). The HCPs have a key role in the identification and reporting of adverse events associated with MD for continued patient safety. The aim of the study is to assess awareness of the recently launched MV Programme in India among the health-care professionals working in a tertiary care teaching hospital. Methods: A questionnaire-based study was conducted among health-care professionals of Viswabharathi Medical College and General Hospital, like residents, interns, nurses (OT, emergency, intensive care unit, etc.), and laboratory technicians of various specialties working in a tertiary care teaching hospital in Kurnool. A pre-validated questionnaire consisting of questions pertaining to knowledge, attitude and practice of MV was circulated to HCPs through Google Forms, and data were recorded and analyzed using statistical tests. Results: One hundred and eighteen doctors responded out of 200 contacted, providing a response rate of 59%. They belonged to medical and allied branches (77), surgical branches (24), and diagnostic branches (17). Sixty-nine (58.5%) doctors strongly agreed that these types of programs are very effective in keeping a check on AE caused by MD. 98 (83%) doctors responded-certainly; we should report all the AEs. Conclusion: This study creates awareness about MV and imparts a reporting culture among the HCPs.